Desenvolvimento de um serious game de educação em saúde bucal com participação de especialistas e usuários - Mendonça, Thaís Silva (2022)
Children have experienced digital technologies since young ages, especially educational games (serious games). With the increase in smartphones, tablets, and computers, applications aimed at health promotion have multiplied. When educational games are appropriately developed, users learn content quickly and efficiently. There is a lack of scientific studies on educational games in pediatric dentistry. It was proposed to regionalize the game Barney's healthy foods, developed internationally for children's oral health education, from the perspectives of specialists and users. This descriptive study was developed in three phases: I) discussion with experts based on the improved version in Jordan; II) development of the first Brazilian version of the game; III) test of the first version with children from 4 to 8 years of age and companions. PHASE I, twelve specialists interested in health education, oral health or health technologies participated in a focus group to assess the relevance of regionalizing the game for Brazil. The transcripts of the specialists' speeches were analyzed by content analysis, which originated categories with the respective main indications of alteration: eating habits - adaptation to the Brazilian context, oral hygiene habits - inclusion of dental floss and attention to the amount of fluoride toothpaste; indicative age group – reduce to 4 to 8 years; characters – change the squirrel for an animal from the Brazilian fauna; objective – to be less prescriptive and to promote the child's autonomy to choose food. PHASE II, the original game's source code was obtained from the University of Jordan. After analyzing the feasibility of the modifications suggested by the experts, the game's programming was changed. A version was obtained with images adapted to Brazil, language in Brazilian Portuguese and content with minor changes. PHASE III, fifteen children (mean age 6.4 years, standard deviation 1.3, 9 boys) played the Brazilian version once, under the observation of the accompanying adults (13 mothers) and the researcher. The global average of correct answers in the game's tasks was 75.3% and ranged from 50.0% to 100%. Children had fun with the game, and most understood the content and its interface. The companions found the information relevant and enjoyed the gameplay for their children. We conclude that the developed Children's Oral Health Game provides relevant information on dental caries prevention after a systematic regionalization process that heard the voices of specialists and users.